Book Review: “When Schools Work” by Bruce Fuller—Decoding Democratic Educational Reforms by Interdisciplinary Research Methods - Wu, Yi (Journal of Theory and Practice of Contemporary Education, 2024)
This essay reviews “When Schools Work: Pluralist Politics and Institutional Reform in Los Angeles” by Professor Bruce Fuller, a comprehensive examination of educational reform in Los Angeles. Fuller’s work, rich in interdisciplinary research methods and grounded in democratic education principles, critically analyzes the initiatives of the 1990s, the rise of charter schools, and the unique socio-political context of Los Angeles. It highlights the importance of community engagement, equitable resource distribution, and the role of grassroots organizations in driving reforms. Fuller’s meticulous approach to research methodology, integrating qualitative data and considering ethical implications, underscores the complexity of educational reform. The book’s insights into the transformative potential of educational policies make it a valuable resource for policymakers, educators, and scholars, offering universal lessons applicable beyond Los Angeles.